1993
DOI: 10.1007/bf01956142
|View full text |Cite
|
Sign up to set email alerts
|

Orocaecal transit time in patients with Crohn disease

Abstract: Orocaecal transit time (OCTT) using the lactulose hydrogen breath test was investigated in 16 patients (age 10-19.4 years) with active Crohn disease (CD). Disease activity was assessed by the paediatric CD activity index (PCDAI). OCTT was prolonged in all patients (mean 149.9 min, SD 32.7) relative to healthy age-matched controls (mean 56.9 min, SD 11.1). PCDAI was increased (median 48.8, range 32.5), indicating moderate to severe disease in all patients. A close correlation between OCTT and PCDAI (Spearman r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Studies (3,24,29) have shown delays in gastric and intestinal transit that cannot be accounted for on the basis of mechanical obstruction and are therefore likely due to inflammation-induced alterations in the motility apparatus. Altered motility in Crohn's disease involves changes in neural control mechanisms (47) as well as alterations in the contractility of intestinal smooth muscle (53); we have previously shown that muscle from the inflamed intestine of Crohn's disease patients exhibits increased contractility in vitro following stimulation by carbachol (53).…”
mentioning
confidence: 99%
“…Studies (3,24,29) have shown delays in gastric and intestinal transit that cannot be accounted for on the basis of mechanical obstruction and are therefore likely due to inflammation-induced alterations in the motility apparatus. Altered motility in Crohn's disease involves changes in neural control mechanisms (47) as well as alterations in the contractility of intestinal smooth muscle (53); we have previously shown that muscle from the inflamed intestine of Crohn's disease patients exhibits increased contractility in vitro following stimulation by carbachol (53).…”
mentioning
confidence: 99%
“…Thus, the measurement of breath H 2 concentrations after the ingestion of lactulose has been used to evaluate OCTT and bacterial overgrowth in the small intestine. [1][2][3][4][5][6][7][8] Because breath H 2 6. a Comparison of the appearance of breath 13 CO 2 and H 2 in a 69-year-old man who had undergone partial gastrectomy for gastric cancer 14 years before this study.…”
Section: Discussionmentioning
confidence: 99%
“…The lactulose hydrogen (H 2 ) breath test (LHBT) has been widely used for the measurement of orocecal transit time (OCTT), [1][2][3] and for the detection of small-bowel bacterial overgrowth and carbohydrate absorption. [4][5][6][7][8] However, the reliability of the LHBT for diagnosing OCTT has been controversial, and factors possibly confounding the reliability of the LHBT require investigation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 OCTTs have been reported to be prolonged in tropical malabsorption. 9 OCTT was reported to be 149.9 min in Crohn's disease, 17 and up to 390 min in patients with cystic fibrosis. 12 Ten percent of the study children were found to be non-hydrogen producers.…”
Section: Discussionmentioning
confidence: 99%